An analysis of stroke risk factors by HIV serostatus in Uganda: Implications for stroke prevention in sub-Saharan Africa - Mbonde, Amir A.; Chang, Jonathan; Musubire, Abdu; Okello, Samson; Kayanja, Adrian; Moses, Acan; Nkwanga, Jacob; Katende, Andrew; Chow, Felicia C.; Saylor, Deanna; O’Carroll, Cumara; Siedner, Mark J. (Journal of Stroke and Cerebrovascular Diseases, 2022)
Objective: HIV infection is an important stroke risk factor in sub-Saharan Africa. However, data on stroke risk factors in the era of antiretroviral therapy (ART) are sparse. We aimed to determine if stroke risk factors differed by HIV serostatus in Uganda. Methods: We conducted a matched cohort study, enrolling persons living with HIV (PWH) with acute stroke, matched by sex and stroke type to HIV uninfected (HIV-) individuals. We collected data on stroke risk factors and fitted logistic regression models for analysis. Results: We enrolled 262 participants:105 PWH and 157 HIV-. The median ART duration was 5 years, and the median CD4 cell count was 214 cells/uL. PWH with ischemic stroke had higher odds of hypertriglyceridemia (AOR 1.63; 95% CI 1.04, 2.55, p=0.03), alcohol consumption (AOR 2.84; 95% CI 1.32, 6.14, p=0.008), and depression (AOR 5.64; 95%CI 1.32, 24.02, p=0.02) while HIV- persons with ischemic stroke were more likely to be > 55 years of age (AOR 0.43; 95%CI 0.20–0.95, p=0.037), have an irregular heart rhythm (AOR 0.31; 95%CI 0.10–0.98, p=0.047) and report low fruit consumption (AOR 0.39; 95%CI 0.18–0.83, p=0.014). Among all participants with hemorrhagic stroke (n=78) we found no differences in the prevalence of risk factors between PWH and HIV-. Conclusions: PWH with ischemic stroke in Uganda present at a younger age, and with a combination of traditional and psychosocial risk factors. By contrast, HIV- persons more commonly present with arrhythmia. A differential approach to stroke prevention might be needed in these populations
Keywords: HIV infection; Stroke; Risk factors; Psychosocial factors; Hypertension; Sub Saharan Africa; Uganda